Unpacking the Layers: Understanding The Multifaceted Nature of L2 Learning Complexity - Aziz, Muhammad Fahruddin; Jayaputri, Herlandri Eka (Soegijapranata Catholic University, 2022)
The impact of age on language learning is often explained by various factors such as neural mechanisms, biological influences, and learning conditions. This study is a literature review that aims to analyze age influences based on various sources, including journals, books, and proceedings. The study argues that there is a cognitive mechanism known as the language defense mechanism that acts as a barrier to maintain the integrity of L1 information, leading to challenges in acquiring L2 for adults. This defense mechanism strengthens as L1 knowledge increases, making it more difficult to learn L2. The concept of the defense mechanism provides another perspective on models such as fossilization, language interference, the impact of age, and bilingualism in the context of learning new languages.